A New Scheme of Representing a Secret Message Using Second Quotient Remainder Theorem in Text Steganography - Osman, Baharudin; Yasin, Azman; Nizam Omar, Mohd (International Journal of Engineering and Technology, 2018)
Steganography is a method of concealing a secret message in a cover medium in such a way that the intruder is not able to detect the existence of the secret message. Due to extensive use of Internet and other communications media, the confidentiality and data integrity need a special means to protect it against unauthorized access. Several schemes were introduced by researchers to represent the value of a hidden message. The first scheme converts a secret message to ASCII code and is represented into x,y form which raises a redundancy representation for a repeating character of the secret message. The second scheme is using the octal value of secret message and converts it into a similar form. Another scheme modifies the previous scheme by adding a â€œ+â€ and â€œ-â€œsymbols. These techniques are resulted in the limited range of the x,y values, repeating representation and a difficulty on generating a stegotext. To overcome the problems, the proposed scheme represents a secret message with a various representation and converts it into x, y, z form. A Second Quotient Remainder Theorem is used to converts the value to x, y, z forms. As a result, the range of the new representation is increased.Â Â
Keywords: Text Steganography; Secret Message; Second Quotient Remainder Theorem.